Correlation of novel ALKATI with ALK immunohistochemistry and clinical outcomes in metastatic melanoma. Issue 4 (15th September 2020) - Shah, Kabeer K; Neff, Jadee L; Erickson, Lori A; Jackson, Rory A; Jenkins, Sarah M; Mansfield, Aaron S; Moser, Justin C; Harris, Antoneicka L; Copland, John A; Halling, Kevin C; Flotte, Thomas J
Abstract : Aims: Recently, a novel isoform of anaplastic lymphoma kinase, with alternative transcription initiation (ALK ATI ), has been described in melanoma and is susceptible to targeted ALK‐inhibitor therapy. Clinical outcomes of patients with ALK ATI mutated melanoma as well as correlation with immunohistochemical (IHC) methods have not yet been described. Methods and results: Clinicopathological characteristics were abstracted for 324 patients with metastatic melanoma (MM). IHC, fluorescence in‐situ hybridisation and RNA‐based digital molecular analysis assays were performed on archival tissue from 173 stage III and 192 stage IV tumours. ALK ATI was identified in 12.7 and 4.8% stage III and IV tumours, respectively. Discrete presentations of the ALK ATI are seen: isolated ALK ATI ( n = 20) and mixed ALK ATI (combined ALK ATI and ALK WT ; n = 7). Isolated ALK WT expression ( n = 4) was seen with no ALK fusions. Stage III patients showed improved survival with ALK ATI expression compared to those with ALK WT or no expression [5‐year survival 80, 95% confidence interval (CI) = 57–100% versus 43%, 95% CI = 34–55%, P = 0.013]. Clinicopathological characteristics were not statistically significant. Strong diffuse cytoplasmic staining of ALK IHC ( n = 12) has a sensitivity of 52.2%, specificity 100%, PPV of 100% and NPV of 92.5% of detecting isolated ALK ATI . Conclusion: Presence of ALK ATI is a good prognostic indicator in MM. ALK IHC and digital molecular analysis can be incorporated into MM evaluation to identify patients with ALK ATI for targeted therapy.